2012
DOI: 10.1186/1742-2094-9-115
|View full text |Cite
|
Sign up to set email alerts
|

A comparative review of cell culture systems for the study of microglial biology in Alzheimer’s disease

Abstract: Over the past two decades, it has become increasingly apparent that Alzheimer’s disease neuropathology is characterized by activated microglia (brain resident macrophages) as well as the classic features of amyloid plaques and neurofibrillary tangles. The intricacy of microglial biology has also become apparent, leading to a heightened research interest in this particular cell type. Over the years a number of different microglial cell culturing techniques have been developed to study either primary mammalian m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
263
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(271 citation statements)
references
References 38 publications
5
263
1
2
Order By: Relevance
“…Inspired by these observations, we studied the effect of nimodipine on microglia in greater detail using two different microglia cell lines (N9 and BV-2). These two cell lines were chosen because their calcium signaling, cytokine production, and cell-cell interactions were reported to be comparable to primary cells (22,23). By applying different doses of nimodipine to N9 and BV-2 cultures for 24 h, we were able to detect a dose-dependent loss of cells.…”
Section: Resultsmentioning
confidence: 78%
“…Inspired by these observations, we studied the effect of nimodipine on microglia in greater detail using two different microglia cell lines (N9 and BV-2). These two cell lines were chosen because their calcium signaling, cytokine production, and cell-cell interactions were reported to be comparable to primary cells (22,23). By applying different doses of nimodipine to N9 and BV-2 cultures for 24 h, we were able to detect a dose-dependent loss of cells.…”
Section: Resultsmentioning
confidence: 78%
“…Experimentally induced inflammation in chronically instrumented non-anesthetized fetal sheep is a well-established and highly translational in vivo model of fetal physiology (Prout et al, 2010(Prout et al, , 2012 Primary microglia cultures in different species have been reported for decades (Stansley et al, 2012). We integrated both in vivo and in vitro models into a new, hybrid system adding the layer of the whole genome analysis using RNAseq.…”
Section: In Vivo-in Vitro Model Of Perinatal Inflammationmentioning
confidence: 99%
“…These cells were selected because it is known that they have many properties similar to primary microglia cultures, which was confirmed in a previous publication. 47,56 Seeing that dPGS was nontoxic in microglia at a concentration of 100 nM (MTT assay, trypan blue exclusion assay and Hoechst 33342 labeling of cell nuclei, see below), we investigated if this lack of toxicity could be explained by their inability to enter the cells and only temporarily bind to plasma membrane putative selectin receptors. 20,53 For this we used dPGS-Cy5 and the control triglycerol-Cy5 (TG-Cy5) and untreated cells (controls for autofluorescence).…”
Section: ■ Introductionmentioning
confidence: 99%